2006
DOI: 10.1007/s10350-006-0620-y
|View full text |Cite
|
Sign up to set email alerts
|

Colon and Rectal Injuries

Abstract: The management of penetrating and blunt colon, rectal, and anal injuries has evolved during the past 150 years. Since the World War II mandate to divert penetrating colon injuries, primary repair or resection and anastomosis have found an increasing role in patients with nondestructive injuries. A critical review of recent literature better defines the role of primary repair and fecal diversion for these injuries and allows for better algorithms for the management of these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 168 publications
(236 reference statements)
0
65
0
6
Order By: Relevance
“…Além do exame físico acurado, o diagnóstico é excluído ou confirmado por uma combinação de métodos, incluindo LPD, FAST e TC, como para as demais vísceras ocas, uma vez que nenhum método atual, isoladamente, é suficiente para concluir o diagnóstico. 13 O emprego de laparoscopia pode ser útil sob alguns aspectos, porém, como já foi discutido, a indicação precisa para seu uso ainda não está completamente estabelecida. 13 A correta abordagem nas lesões de cólon vem sendo debatida e tem evoluído ao longo das últimas décadas.…”
Section: -Lesão Traumática De Cólon E Retounclassified
“…Além do exame físico acurado, o diagnóstico é excluído ou confirmado por uma combinação de métodos, incluindo LPD, FAST e TC, como para as demais vísceras ocas, uma vez que nenhum método atual, isoladamente, é suficiente para concluir o diagnóstico. 13 O emprego de laparoscopia pode ser útil sob alguns aspectos, porém, como já foi discutido, a indicação precisa para seu uso ainda não está completamente estabelecida. 13 A correta abordagem nas lesões de cólon vem sendo debatida e tem evoluído ao longo das últimas décadas.…”
Section: -Lesão Traumática De Cólon E Retounclassified
“…4 Colon trauma, once considered a universally fatal injury, has seen a significant decline in mortality over the last 70 years due to the advancement of antibiotics, blood component resuscitation, and the expeditious repair of injuries to prevent fecal contamination. 5 In the most severely injured patients, damage control surgery (DCS) with emphasis on stopping life-threatening hemorrhage, controlling enteric spillage, and focused, expeditious patient resuscitation, has been successfully applied in the civilian and military trauma settings. [6][7][8][9] While DCS undoubtedly saves lives when judicially applied, how the well-established practice of fecal diversion relates to the newer wartime damage control techniques remains uncertain.…”
mentioning
confidence: 99%
“…[1] Although rectal injuries are rarely encountered, they are associated with high morbidity and mortality rates. [2] The principles of the treatment of rectal injuries have been determined based on the experiences gained from high-energy injuries during wartime. Since the injuries in civilian life are low-energy injuries, direct adaptation of these principles to civilian injuries has begun to be questioned.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further examinations should be performed in cases of suspected rectal injuries, including cystourethrograms, abdominal and pelvic X-rays, water-soluble contrast studies, peritoneal lavage, and computed tomography (CT) scanning. [2] In the treatment of extraperitoneal rectal injuries, a diverting colostomy has been accepted as the standard therapy by many authors. [7][8][9] It has been reported that extraperitoneal rectal injuries can be safely treated with fecal diversion alone, particularly in low-velocity trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation